Performance of cement-stabilized Singapore clays under low temperature - Saku, Nikhila (Nanyang Technological University, 2020)
Cement stabilization is widely used to treat soft clay in Singapore for different applications. Previous studies only focus on the performance of cement-stabilized clay under ambient temperature. This FYP project is based on an industry-funded research project, which attempts to use cement stabilization technique to improve the Singapore clay for liquefied natural gas (LNG) storage underground. For this application, the cement-stabilized clay may work under a temperature lower than 0◦C. Hence, this project investigated the performance of cement-stabilized Singapore clay under low temperature through laboratory testing. Two cement to dry soil ratios of 0.2 and 0.3 were used and all samples were cured for 28 days at 24℃ after which samples were spilt into 3 groups for further curing at temperatures of 24℃, -6℃ and -12℃. The properties namely, bulk density, unconfined compressive strength and thermal conductivity were measured for the cement-stabilized clay to evaluate its performance. The test results revealed that the thermal insulation performance worsened with decreasing temperature as steady increases in thermal conductivity and diffusivity were observed. However, the performance of mechanical properties of cement stabilized clays mostly improved under low temperatures. The results saw more ductile behavior at lower temperatures and maximum unconfined compressive strength attained at a temperature of -6℃.